Prospective Associations of Dietary Intakes of Total Antioxidant Capacity and Its Subclasses With Metabolic Syndrome in Adults Aged 40 Years and Older. (7th June 2021) - Kong, Ji-Sook; Kim, Youngjun; Lee, Jiseon; Woo, Hye Won; Shin, Min-Ho; Shin, Dong Hoon; Koh, Sang Baek; Kim, Hyeon Chang; Choi, Bo Youl; Kim, Mi Kyung
Abstract: Objectives: This study aimed to evaluate the association between dietary intakes of total antioxidant capacity (TAC) and its subclasses (flavonoids and its individual subclass and individual vitamins) and incidence risk of Metabolic syndrome (MetS) in the KoGES_CArdioVascular disease Association Study (CAVAS). Methods: A total of 11, 272 participants over 40 years of age who did not have MetS from CAVAS were enrolled. Cumulative average TAC and flavonoid intake were calculated from repeated food frequency questionnaires composed of 106 items using data during follow-up. Using a modified Poisson regression model, we estimated incidence rate ratios (IRRs) and 95% confidence intervals (CIs) for MetS in men and women separately and subsequently pooled these results. Results: Over 56, 425 person-year of follow-up, there were 2, 218 incident cases of MetS. While both TAC and flavonoids were inversely associated with MetS development in the pooled multivariable analysis (fourth vs. first quartile, IRR: 0.88; 95% CI 0.76–1.01 for TAC and 0.83, 0.73, 0.95 for flavonoids), there were relatively clear inverse associations between intake of certain subclasses and incidence of MetS. Among flavanones, theaflavins, anthocyanins, and carotenoids were obvious inversely associated with MetS (0.57; 0.50, 0.65 for flavanones, 0.55; 0.48, 0.63 for anthocyanins, 0.60; 0.52, 0.69 for carotenoids). However, the associations were relatively weak in flavones and flavonols (0.96; 0.84, 1.10 for flavones and 0.84; 0.73, 0.96 for flavonols). Conclusions: Intake of specific antioxidants such as flavanones, anthocyanins, carotenoids may provide health benefits in preventing MetS. More prospective studies are warranted to elucidate the association between TAC and individual subclasses and the incidence of MetS and chronic disease. Funding Sources: This work was supported by the Research Program funded by the Korea Centers for Disease Control and Prevention (2004-E71004–00, 2005-E71011–00, 2006-E71009–00, 2007-E71002–00, 2008-E71004–00, 2009-E71006–00, 2010-E71003–00, 2011-E71002–00, 2012-E71007–00, 2013-E71008–00, 2014-E71006–00, 2014-E71006–01, 2016-E71001–00, 2017N-E71001–00) and was supported the National Research Foundation of Korea(NRF) grant funded by the Korea government (MSIT) (No. NRF-2020R1A2C1004815).